2016
DOI: 10.15441/ceem.15.114
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between an instructor-led course and training using a voice advisory manikin in initial cardiopulmonary resuscitation skill acquisition

Abstract: Objective We compared training using a voice advisory manikin (VAM) with an instructor-led (IL) course in terms of acquisition of initial cardiopulmonary resuscitation (CPR) skills, as defined by the 2010 resuscitation guidelines.Methods This study was a randomized, controlled, blinded, parallel-group trial. We recruited 82 first-year emergency medical technician students and distributed them randomly into two groups: the IL group (n = 41) and the VAM group (n = 37). In the IL-group, participants were trained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…9 Furthermore, it was also explained that the application of practice while watching and hands-on experience method will improve psychomotor skill of CPR. 5 CPR training for students reduced fear in doing first aid upon emergency case. Students had quite enough cognitive and physical skills to play role as first aider in emergency case specifically in cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Furthermore, it was also explained that the application of practice while watching and hands-on experience method will improve psychomotor skill of CPR. 5 CPR training for students reduced fear in doing first aid upon emergency case. Students had quite enough cognitive and physical skills to play role as first aider in emergency case specifically in cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…4 Hence, education and training for first aider becomes an essential matter. 5 Training and education on CPR will be more optimal when it is given to students. Students have been capable in receiving materials regarding first aid and emergency prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the method of practice while watching and hands-on experience would increase the psycho-motoric skill in CPR. 6 The first-aid training to the senior high school students decreased the fear in giving the rescue in the cases of emergency. The senior high school students possessed enough cognitive and physical skill as the first responder of the emergency case, especially cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…5 Therefore, the education and training for the first responder became an important matter. 6 The training and education about CPR will be more optimum if it is given to students in the level of senior high school. The students in the age of more or less 17 years are able to understand the materials of the first aid and handling the emergency situation.…”
Section: Background and Significancementioning
confidence: 99%
“…322,326 One study showed worse CPR performance at the conclusion of training, although this study has a high risk of bias because of unclear outcome definitions and the use of the audiovisual feedback system to replace an instructor. 321 One observational study found improvements in delivered chest compression rate (118.61 +/10.74 compressions/min versus 137.72 AE 11.14 compressions/min; P < 0.001), with the use of a feedback device during training of student teachers. 325…”
Section: Cpr Performance From Training Conclusion To 1 Year Aftermentioning
confidence: 99%